(untitled) (Praxis Educativa, 2024)
We present the initial findings of an ethnographic investigation on the use of teaching materials by educators who teach Language and Literature to deaf students in bilingual schools. This study documents three types of tensions (curricular, material conditions of teaching, and teacher training) and practices related to the production, reuse, and storage of teaching materials that have not previously been documented. The two main outcomes of this initial examination are as follows: (i) the significance of the practices involving teaching materials is contingent on the tensions we have identified, and (ii) highly specialized practices and knowledge circulate within the schools, but remain concealed externally, which highlights a gap between what is documented and what is not. That is to say: the practical knowledge acquired by teachers in the field is not part of teacher training practices nor does it serve as input for educational policies.